On the Problem of Employment in tne Rural Areas of RA - Gyozalyan, Vardush (Bulletin of Yerevan University G: Economics, 2014)
In the Economy of RA, the problem of employment, especially in the rural areas, in the context of overcoming the poverty and the increasing migration, takes on special significance. The main problems and features, related to the employment in the rural areas of RA, are considered in the article. The author observes, that by the reason of low productivity in the field of agriculture, in the villages of Armenia under the condition of high employment level, the level of income is very low, and in its turn it becomes the reason of high rural poverty level. Within the scope of this article the author suggests definite ways for solving the problem.
Keywords: employment, poverty, rural population, agriculture